How does financial literacy influence undergraduates’ risk-taking propensity? - Molina-García, Antonio; Cisneros-Ruiz, Ana José; López-Subires, María Deseada; Diéguez-Soto, Julio (Elsevier, 2023)
Previous evidence is contradictory about the financial literacy-individual’s risk-taking propensity relationship. Therefore, this article attempts to examine the relationship between financial literacy and risk-taking propensity in a university environment, considering for the first time the financial literacy’s multidimensional nature (i.e., financial knowledge, financial attitude, and financial behaviour). Applying Covariance-Based Structural Equation Models to 568 Spanish undergraduates, our results show that: (1) financial knowledge and financial behaviour directly and positively affect risk-taking propensity; (2) financial attitude indirectly and positively affects risk-taking propensity through financial behaviour. These findings are relevant since they provide new insights into the association mechanism that explains the financial literacy-undergraduates’ risk-taking propensity relationship.
Keywords: Finanzas - Estudio y enseñanza superior; Financial literacy; Financial knowledge; Financial behaviour; Financial attitude; Risk-taking propensity; Undergraduates